Penggambaran Sosok-sosok Ideal Masa Jawa Kuno: Tinjauan Relief Gua Selomangleng Tulungagung - Izza, Nainunis Aulia (Paradigma: Jurnal Kajian Budaya, 2022)
This study examines Ancient Java’s ideal figures based on seven panels of the Arjunawiwaha story from Selomangleng Tulungagung Cave. The discussion focuses on the use of archaeological data, which are reliefs, statues, and the description of ideal figures from Ancient Java Kakawin. The results show that all the figures in the Selomangleng Tulungagung Cave depicted the protagonist figures from Arjunawiwaha without showing the antagonist. The protagonist figures consist of God Indra, Arjuna, Nymphs, Soldiers, and God Shiva disguised as a sage. The protagonist figures displayed the ideal concept of figures related to their role. The relief depicted the stratification of gods and humans, Arjuna as an ideal leader and male, angels as ideal woman, ideal marriage, and changes of Arjuna’s strata from human to superhuman who can reach heaven after defeating Niwatawakaca. A lot of the reliefs of Arjunawiwaha that are carved are a strong indication that Arjuna was an idol in the ancient Javanese era.